Sphenopalatine ganglion block: Intranasal transmucosal approach for anterior scalp blockade - A prospective randomized comparative study - Narmada Padhy; Srilata Moningi; Dilip K Kulkarni; Rajesh Alugolu; Srikanth Inturi; Gopinath Ramachandran (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Peripheral nerve blocks in neurosurgical practice attenuate most stressful responses like pin insertion, skin, and dural incision. Scalp block is conventionally the blockade of choice. Further studies for less invasive techniques are required. Intranasal transmucosal block of the sphenopalatine ganglion has shown promising results in patients with chronic headache and facial pain. The primary objective of our study was to compare the gold standard scalp block and bilateral sphenopalatine ganglion block (nasal approach) for attenuation of hemodynamic response to pin insertion. Secondary objectives included hemodynamic response to skin and dural incision. Material and Methods: After IRB approval and informed consent, a prospective randomized comparative study was carried out on 50 adult patients undergoing elective supratentorial surgery. The hemodynamic response to pin insertion, skin incision, and dural incision was noted in both the groups. The data was analyzed with NCSS version 9.0 statistical software. Results: The HR and MAP were comparable between the groups. Following dural incision MAP was significantly lower at 1,2,3,4,5 and 10 min in group SPG whereas in group S it was significantly lower at 1 and 2min. (P = 0.02 at T1, P = 0.03 at T2). Conclusions: Concomitant use of bilateral SPG block with general anesthesia is an effective and safe alternative technique to scalp blockade for obtundation of hemodynamic responses due to noxious stimulus during craniotomy surgeries.